PENGARUH ETOS KERJA, INSENTIF, DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA UD MADIA JAYA SINGARAJA - Rianita, Ni Made; Ayuni, Luh Dita (Jurnal Daya Saing, 2023)
This study aims to determine the effect of work ethic, incentives, and career development onemployee performance at UD Madia Jaya Singaraja. The data analysis technique used in this study wasmultiple linear regression analysis, classical assumption test, model goodness-of-fit test and hypothesis test(T-Test) using the SPSS Version 21.0 application for windows. The results of this study indicate that theeffect of the work ethic on employee performance at UD Madia Jaya Singaraja is 0.446 and the results oftesting the hypothesis with the t-test show that t-test > t-table (2.091 > 1.666). The effect of incentives onemployee performance at UD Madia Jaya Singaraja was 0.359 and the results of testing the hypothesis withthe t-test found that t-test > t-table (2.045 > 1.666). The effect of career development on employeeperformance at UD Madia Jaya Singaraja has a regression value of 0.154 units and the results of testing thehypothesis with the T-test show that t-test > t-table (4.800 > 1.666). The results of calculations from the Ftest > F-table, (45.231 > 3.13), this indicates that the work ethic, incentives and career development have ajoint effect on employee performance with a significant level of 0.000 < 0.050.